The New Media, an Ironic Reality as a Review of Social Consciousness in Nigerian Movies: A Case Study of Femi Adebayo’s Jagunjagun - Afolabi Amos Adelekan; Taiwo Adekemi Agnes (Britain International for Academic Research (BIAR-Publisher), 2023)
This paper examines the new media as a set to make viral or bring to the knowledge of what is happening in our society within a short period of time. This paper uncovers the hidden biases and brings out the ironic reality or awakens the social consciousness of the people through the movie Jagunjagun produced by Femi Adebayo. In achieving this, the paper adopted social contructionism theory to critically analyse the movie. However, the qualitative research method through a content analysis of Femi Adebayo’s movie Jagunjagun is used with the objectives of analyzing the effectiveness of the new media to uncover the hidden biases in the movie and at the same time, awakens the social consciousness of the people living in the same society. Consequently, it is discovered that the movie (Jagunjagun) is full of ironic reality of the Nigerian social political milieu.